Decision Support System for The Feasibility of Giving Customer Credit Using Topsis and Saw Methods (case Study): Save Loan Cooperative CV. the Source of Prosperous Life - M Mahaputra Hidayat; Mas Nurul Hamidah; Ayu Nur (JEECS (Journal of Electrical Engineering and Computer Sciences), 2019)
Supporting System for Deciding the Feasibility of Providing Credit to Customers with Topsis Method andSimple Additive Weighting Method in CV. Sumber Hidup Prosperous, this research is motivated by the results of acustomer who must meet the criteria determined by the cooperative to be able to get credit. In this case cooperativesare required to be able to make decisions quickly and carefully. To realize this it is necessary to have a decisionsupport system (SPK) with the Topsis method and the Simple Additive Weighting method that can solve the problemof decision making with many criteria. The results obtained from this study are the application program of the DecisionSupport System for Providing Credit to the Customer with the Topsis Method and the Simple Additive WeightingMethod in CV. The Source of Prosperous Life. The conclusions of the results of this study have shown a value that isaccurate enough to help simplify the process of creditworthiness and report generation.